2016
DOI: 10.1002/adma.201505473
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Molecular Ordering in Aqueous Conducting Polymers Using Ionic Liquids

Abstract: The molecular ordering of aqueous conducting polymers is controlled using a rational method. By introducing various ionic liquids, which have designed electrostatic interactions to PEDOT:PSS solutions, the evolution of the molecular ordering of the PEDOT is manipulated. Consequently, highly ordered nanostructures are achieved with a reduced π-π stacking distance of ≈3.38 Å and, thus, a maximum σ of ≈2100 S cm .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
239
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(269 citation statements)
references
References 30 publications
29
239
1
Order By: Relevance
“…Figure b displays the conductivity of PEDOT:PSS films with different added amount of [EMIM][TCM]. In general, the PEDOT:PSS with [EMIM][TCM] composites exhibit substantially higher conductivities, which correlates well with previous studies where ionic liquids are showed to be good conductivity enhancers in conducting polymers . For instance, at 1.5 wt% [EMIM][TCM], the measured conductivity is around 1000 S cm −1 which is almost three orders of magnitude higher than that of the pristine PEDOT:PSS film (appropriate 1 S cm −1 ).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Figure b displays the conductivity of PEDOT:PSS films with different added amount of [EMIM][TCM]. In general, the PEDOT:PSS with [EMIM][TCM] composites exhibit substantially higher conductivities, which correlates well with previous studies where ionic liquids are showed to be good conductivity enhancers in conducting polymers . For instance, at 1.5 wt% [EMIM][TCM], the measured conductivity is around 1000 S cm −1 which is almost three orders of magnitude higher than that of the pristine PEDOT:PSS film (appropriate 1 S cm −1 ).…”
supporting
confidence: 81%
“…The current state‐of‐the‐art active conjugated polymer for OECTs is poly(3,4‐ethylenedioxythiophene) (PEDOT) which is commonly charge compensated by an immobile polymer anion, polystyrenesulphonate (PSS), Figure a . The pristine PEDOT:PSS thin films typically suffer from low electrical performance (conductivity: ≈1 S cm −1 ; hole mobility: 10 −3 cm 2 V −1 s −1 ), due to excessive insulating PSS content and lack of dense packing of PEDOT chains. One commonly used strategy is the addition of co‐solvent dispersion additive, ethylene glycol (EG), which leads to an increase in PEDOT aggregation or structural reorganization of the PEDOT domains into more continuous network and thus enhances the charge carrier mobility ( µ ) .…”
mentioning
confidence: 99%
“…Graphene and CNTs suffer from high sheet resistance due to low intrinsic carrier concentration and high contact resistance, respectively . PEDOT:PSS shows high sheet resistance as well because of its low inherent electrical conductivity (σ dc ≈ 10 0 S cm −1 ) . Among the aforementioned materials, silver nanowire (AgNW) transparent electrodes underscore the potential to replace ITO, because they provide a tradeoff between conductivity and transparency, flexibility, and solution processability.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we had expected Au vapor deposition to give low contact resistance but it turns out to be a poor match with the important factors for the legs’ performance optimizations, such as having DMSO addition to PEDOT:PSS and the ball-milled TTF-TCNQ without PVC. This result suggests that we need to explore non-volatile additives to PEDOT:PSS [18] and polymer-based n-type materials soluble to common solvents [19].
10.1080/14686996.2018.1487239-F0008Figure 8.Schematic of the Au penetrated π-type TE module.
…”
Section: Resultsmentioning
confidence: 99%